Simulasi Perancangan Simulasi Perancangan dan Implementasi Redundant Link Multi Protocol Label Switching (MPLS) Virtual Private Network (VPN) Menggunakan Mikrotik Router OS - Andi Suprianto; Radiansyah Akbar (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2022)
Currently the need for information and communication technology has grown rapidly, especially in the field of communication and network services. PT. Indonesia Comnets Plus as a service provider requires a good network for sending data from the head office, namely the Cawang office to the branch office in Duren Tiga. PT. Indonesia Comnets Plus wants the Cawang office as the center to have a main link and backup so that when the main link goes out, the Cawang office can still operate using a backup link. One of the concepts that can be applied to overcome these problems is to use the redundant link method by implementing a main link system and automatic backup links. Main link and backup link systems can be applied to MPLS VPN by using Border Gateway Protocol (BGP) routing by adding the AS PATH Prepend attribute. This research will implement Multi Protocol Label Switching (MPLS) Virtual Private Network (VPN) Redundant Link and conduct tests to ensure that the main link and backup link have been implemented correctly, and between the Cawang office and Duren Tiga office can communicate using the main link. as well as backup paths that have been implemented Key Word: main link, backup link, mpls-vpn, routing bgp, aspath prepend